2020
DOI: 10.3847/1538-4357/ab9e66
|View full text |Cite
|
Sign up to set email alerts
|

SN 2019ehk: A Double-peaked Ca-rich Transient with Luminous X-Ray Emission and Shock-ionized Spectral Features

Abstract: We present panchromatic observations and modeling of the Calcium-rich supernova (SN) 2019ehk in the starforming galaxy M100 (d≈16.2 Mpc) starting 10 hr after explosion and continuing for ∼300 days. SN 2019ehk shows a double-peaked optical light curve peaking at t=3 and 15 days. The first peak is coincident with luminous, rapidly decaying Swift-XRT-discovered X-ray emission (»-L 10 erg s x 41 1 at 3 days; L x ∝t −3), and a Shane/Kast spectral detection of narrow Hα and He II emission lines (v≈500 km s 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 152 publications
2
45
0
Order By: Relevance
“…Our current sample of Ca-rich SNe offsets is based on the sample from our original characterization study (Perets et al 2010) based on SNe from the LOSS and CCCP surveys, and the additional Ca-rich SNe discovered by the PTF/iPTF (Kasliwal et al 2012;Lunnan et al 2017;De et al 2018), PESSTO (Valenti et al 2014) and ZTF (De et al 2020;Jacobson-Galán et al 2020 surveys. The SNe offsets are taken from these studies, and summarized in Table 1; the cumulative The cumulative offset distributions of sGRBs and Ca-rich supernovae in early-and late-type galaxies.…”
Section: Ca-rich Supernovae Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Our current sample of Ca-rich SNe offsets is based on the sample from our original characterization study (Perets et al 2010) based on SNe from the LOSS and CCCP surveys, and the additional Ca-rich SNe discovered by the PTF/iPTF (Kasliwal et al 2012;Lunnan et al 2017;De et al 2018), PESSTO (Valenti et al 2014) and ZTF (De et al 2020;Jacobson-Galán et al 2020 surveys. The SNe offsets are taken from these studies, and summarized in Table 1; the cumulative The cumulative offset distributions of sGRBs and Ca-rich supernovae in early-and late-type galaxies.…”
Section: Ca-rich Supernovae Samplementioning
confidence: 99%
“…These might even relate to the intracluster regions where they were found. Indeed, ∼ 15 − 20 per cent of type Ia SNe in clusters are found in the intracluster medium far from any host galaxy(Gal-Yam et al 2003;Sand et al 2011).We note that various SNe with only partial similarities to faint, type Ib, Ca-rich SNe characteristics were discussed in the literature (see e.g De et al 2020;Jacobson-Galán et al 2020. for recent overviews, and references therein); these are not considered in our sample of bona-fide Ca-rich SNe).…”
mentioning
confidence: 94%
“…More recently, similar structures involving extended material have been invoked to explain a wide variety of transient events (e.g., De et al 2018a;Taddia et al 2018;Fremling et al 2019;Ho et al 2020;Jacobson-Galán et al 2020;Yao et al 2020). Constraining the mass and radius of extended material usually involves comparing the observations to rough analytic scalings or fitting semianalytic models (Nakar & Piro 2014;Piro 2015;Nagy & Vinkó 2016;Sapir & Waxman 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with canonical SNe Ibc, we expect light curves of ultra-stripped SNe to be rapidly evolving and subluminous due to the small amount of M ej and M Ni produced. Among the group of faint and fast objects, SN2005ek (Drout et al 2013), SN2010X (Kasliwal et al 2010), as well as some of the calcium-rich gap transients including PTF10iuv (Kasliwal et al 2012), iPTF16hgs (De et al 2018b), and SN2019ehk (Jacobson-Galán et al 2020;Nakaoka et al 2020) have been suggested as good candidates for ultra-stripped SNe (Moriya et al 2017). However, properties of these objects are also consistent with alternative interpretations, including corecollapse of stars with extended hydrogen-free envelopes (Kleiser & Kasen 2014;Kleiser et al 2018aKleiser et al , 2018b, and explosive detonation of a helium shell on the surface of white dwarfs (Shen et al 2010;Sim et al 2012;Jacobson-Galán et al 2019;Polin et al 2019;.…”
Section: Introductionmentioning
confidence: 99%